Home advantage in Portuguese football: effects of level of competition and mid-term trends. (4th May 2017) - Almeida, Carlos H.; Volossovitch, Anna
Abstract: This study aimed to examine the influence of level of competition (amateur, semi-professional and professional) on the magnitude of home advantage (HA) in Portuguese football, and to verify whether the HA has changed over time. Archival data from 32, 400 matches contested in the three levels of competition over 11 seasons (from 2005/2006 to 2015/2016) were analysed. HA was quantified each season for each league as the number of points won at home expressed as a percentage of all points won at home and away. The mean values of HA were significantly greater than 50% in all levels of Portuguese football ( p  < .001). One-way repeated-measures ANOVA showed a significant effect of competitive level on HA ( p  < .05). In the professional league, the HA was significantly lower (58.31%) than in amateur and semi-professional competitive levels (60.36 and 60.46%, respectively). Altogether, a declining HA effect was found in Portuguese football in recent years. However, negative linear relationships between HA and time were only significant at amateur and semi-professional levels ( p  < .05), while the decline in the major professional league has already started to level off. These findings demonstrate that the advantage of playing at home is losing importance in Portugal. The declining effect of HA, previously evidenced in major professional leagues, has been mirrored by a similar decline at amateur and semi-professional levels within the country. Future research should confirm whether the trends identified in Portugal are also verified in football leagues of other countries.